Black Men in Law School - Jackson, Darrell D., author.
1 online resource (192 pages)
Keywords: "Grounded in Critical Race Theory (CRT), Black Men in Law School refutes the claim that when African American law students are "mismatched" with more selective law schools, the result is lower levels of achievement and success. Presenting personal narratives and counter-stories, Jackson demonstrates the inadequacy of the mismatch theory and deconstructs the ways race is constructed within American public law schools. Calling for a replacement to mismatch theory, Jackson offers an alternative theory that considers marginalized student perspectives and crystallizes the nuances and impact that historically exclusionary institutions and systems have on African American law school students. To further the debate on affirmative action, this book shows that experiences and voices of African American law school students are a crucial ingredient in the debate on race and how it functions in law schools. "--Provided by publisher.